Estimasi asupan indeks glikemik dan beban glikemik dengan kontrol gula darah pasien diabetes melitus tipe 2 - Sinta Mukti Permatasari; Toto Sudargo; Luthfan Budi Purnomo (Jurnal Gizi Klinik Indonesia, 2015)
Background: Non-infectious disease (NID) has become a public health problem both globally, regionally, nasionally, and locally. One of NID that takes a lot of attention is diabetes mellitus (DM). Risk of complication is higher due to lack of attention to lifestyle including diet. The concept of the glycemic index classifies carbohydrate is considered better in controlling blood sugar. However, some studies say otherwise. Therefore, research needs to be done by combining carbohydrate quantity concept (glycemic load) and glycemic indexObjective: To identify the relationship between estimated dietary glycemic index and glycemic load with blood sugar control, as well as to identify other factors associated with glycemic control of patients with type 2 diabetes mellitusMethod: This is an observational study with cross-sectional design. The population study were all outpatients with type 2 diabetes mellitus in Dr.Sardjito hospital Yogyakarta in 2014. Sampling method using a consecutive sampling with sample size of 79 people. Interviews regarding the identity of the respondents through questionnaires, physical activity (IPAQ), and semi-quantitative food frequency (SQFFQ). Blood sugar control (HbA1C) obtained from respondent’s medical record. The data were processed using univariable analysis (descriptive), bivariate (chi-square), and multivariate (GLM)Results: Most respondents were blood sugar uncontrolled (84,81%). Average of dietary GI and GL was 63,26±3,23 and 127,65±43,02. Bivariate test showed that the dietary GI and GL each has a RP value 1,023 and 1,002, and statistically significant (p<0,05) with HbA1C. The prevalence of uncontrolled blood sugar 4,18 times greater in respondents who doesn’t have appropriate eating schedule. Duration of diabetes, nutritional status, physical activity, and education level did not significantly influence HbA1C (p>0,05)Conclusion: There is a relationship between dietary GI, GL, and eating schedule with blood sugar control (HbA1C), but there was no correlation between duration of diabetes, nutritional status, physical activity, and education level with blood sugar control (HbA1C)